METODE KONVENSIONAL, KINESIOTAPING, DAN MOTOR RELEARNING PROGRAMME BERBEDA EFEKTIVITAS DALAM MENINGKATKAN POLA JALAN PASIEN POST STROKE DI KLINIK ONTOSENO MALANG - Sondang Irawan, Dimas; Adiputra, Nyoman; Irfan, Muhammad (Sport and Fitness Journal, 2014)
Stroke patient would have impaired activities of daily living. One-sided weakness of extremities, poor body control, and gait instability. Rehabilitation in stroke patient, effective and can improve the function of the impaired limb. Exercise can provide the functional activity of learning and apply the basic premise that the capacity of the brain is able to reorganize and adaptable so with targeted exercises it can be improved. This study aimed to compare the efficiacy of conventional methods, applications kinesiotaping, and MRP method in improving the gait pattern of stroke patients. The study has pre and post test with control group design using 3 groups. There are 10 people in each group. The first group was given conventional intervention methods, group II given Kinesiotaping application, and the third group was given the intervention using the MRP  with duration of exercise 3 times a week with a time of 60 minutes for 4 weeks. Data in the form of pre-test and post-test patterns of stroke patients analized by using Wisconsin Gait Scale. Samples were 30 divided into 3 groups. In the conventional group had a mean age of 62.3 years with a number of men 5 men and 5 women. At Kinesiotaping group had a mean age of 65.1 years with a number 6 men and 4 women. While the MRP group had a mean age of 62.6 years with a number 6 men and 4 women. Results of hypothesis testing using Anova showed a significant difference between the (average of the WGS scores after intevention of the three groups, with value of p<0,05. The comparison on each method showed that the Kinesiotaping application and MRP have significant difference, but the Kinesiotaping application showed no significally difference with MRP. The conclusions in this study that the conventional methods, Kinesiotaping application and MRP has different efficacy on improfing gait pattern of stroke patient.
Keywords: Conventional, Kinesiotaping, Motor Relearning Programme, Stroke